Potential of radiological investigation in diagnostics of chronic pancreatitis complications - Yu. A. Stepanova; G. G. Karmazanovsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine the role and potential of radiological methods of investigation in diagnostics of complications of chronic pancreatitis.Materials and methods. Results of investigation and treatment of 102 patients who were undergoing treatment in A.V. Vishnevsky Institute of surgery with suspected cystic lesion of the pancreas were analyzed. Age of patients ranged from 15 to 75 years. Men (68,6%) prevailed. All patients had complex radiological investigation including: complex ultrasound investigation included B-mode study, duplex scanning of the main visceral vessels, investigation of hemodynamics around the focus and blood flow within the structure, three-dimensional reconstruction of ultrasound plotting; helical computer tomography with bolus contrast enhancement and magnetic-resonance tomography with bolus contrast enhancement were carried out.Results. Chronic pancreatitis which has become complicated by postnecrotic cyst (or cysts) has been preoperatively diagnosed in 99 cases, in 3 – cystic tumor of pancreas. All patients were operated, lesions have been morphologically verified. At revealing of postnecrotic pancreatic cyst in one case the diagnosis has been put incorrectly, that was caused by atypical pattern of tumor and severe portal hypertension. For 3 patients (age 15 to 34 years) at preoperative stage cystic tumor was diagnosed on a basing on the absence of severe inflammatory changes of parenchyma of the pancreas. However at morphological study resected lesions have been verified as postnecrotic cyst. In 10 cases postnecrotic cyst which has become complicated by arrosive bleeding in its lumen from the adjacent main vessel was diagnosed. In 3 cases postnecrotic cyst was combined with the cystic duodenal dystrophy.Conclusions. Sensitivity, specificity and accuracy ultrasound, computer tomography and magnetic-resonance investigations in revealing of chronic pancreatitis complicated by postnecrotic cyst, was 95,5, 90,5 and 94,8% respectively.